2012
DOI: 10.3846/13923730.2012.700943
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heat Reflective Coatings on Heat Flows Through the Ventilated Roof With Steel Coatings

Abstract: Abstract. In many EU countries, the normative requirements for thermal characteristics of roofs are associated only with rating the heat losses through the roofs during the heating period. The problem of overheated premises under the lightweight ventilated roofs, covered with steel sheets, arises in the summer time. During this period of the year, because of the intensive solar radiation and high air temperature, the steel roof coatings heat up during the day and cause additional heat inflows to the premises. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…(Givoni, 1969;Rawat & Singh, 2022;Synnefa et al, 2012) Emisividad Variación de la reemisión de calor al interior del espacio. (Banionis et al, 2012;Biwole et al, 2008;Černe & Medved, 2007;Givoni, 1969;Kośny et al, 2012) Separación entre las láminas de la cámara Incidencia en la fricción y en la velocidad del aire al interior de la cámara. (Chang et al, 2008;Ciampi et al, 2005;Dimoudi et al, 2006;Lee et al, 2009;Manca et al, 2014;May Tzuc et al, 2019) ACE, 18 (52) CC BY-ND 3.0 ES | UPC Barcelona, España | Variables de diseño de cubiertas ventiladas metálicas en el clima cálido húmedo | https://dx.doi.org/10.5821/ace.18.52.11811…”
Section: Variables Convección Radiación Conducciónunclassified
“…(Givoni, 1969;Rawat & Singh, 2022;Synnefa et al, 2012) Emisividad Variación de la reemisión de calor al interior del espacio. (Banionis et al, 2012;Biwole et al, 2008;Černe & Medved, 2007;Givoni, 1969;Kośny et al, 2012) Separación entre las láminas de la cámara Incidencia en la fricción y en la velocidad del aire al interior de la cámara. (Chang et al, 2008;Ciampi et al, 2005;Dimoudi et al, 2006;Lee et al, 2009;Manca et al, 2014;May Tzuc et al, 2019) ACE, 18 (52) CC BY-ND 3.0 ES | UPC Barcelona, España | Variables de diseño de cubiertas ventiladas metálicas en el clima cálido húmedo | https://dx.doi.org/10.5821/ace.18.52.11811…”
Section: Variables Convección Radiación Conducciónunclassified
“…Meanwhile, the rate of entry of solar heat is the largest contributor to indoor heat and needs to be conditioned so as not to disturb thermal comfort, this needs to be considered, especially from the side of the building roof (Leonardus Murialdo Fransiskus Purwanto 2019). The choice of building materials, roof covering color, roof construction, ceiling covering and dampening efforts need to be carefully considered so that the building becomes more comfortable and shadier (Banionis et al 2012;Ashhar and Lim 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Li [2016] studied that the effect of the ventilated layer of the roof was strong on the themperature delay of the roof, but it was weak on the delay time. Banionis [2012] showed that installing radiant barriers with low emissivity coefficient into the roof construction reduced the additional radiative heat flow caused by the interior surface of the roofs coating into the building. This paper illustrates a numerical investigation on a prototypal ventilated roof for residential use, under summer and winter conditions.…”
Section: Introductionmentioning
confidence: 99%